Acceptance of chronic pain in depressed patients with HIV: correlations with activity, functioning, and emotional distress. Issue 10 (3rd October 2022) - Moitra, Ethan; Stein, Michael D.; Busch, Andrew M.; Pinkston, Megan M.; Abrantes, Ana M.; Baker, Jason V.; Weisberg, Risa B.; Anderson, Bradley J.; Uebelacker, Lisa A.
ABSTRACT: Chronic pain is highly prevalent among persons with HIV (PWH), as is depression. Both comorbidities might contribute to, as well as be maintained by, avoidance-based coping. A promising alternative to avoidance-based coping is acceptance. Acceptance of pain is associated with improved functioning and quality of life in chronic pain patients, but this relationship has not been substantially explored among PWH. Cross-sectional data from 187 adult outpatients enrolled in a randomized trial for depressed PWH with chronic pain were analyzed. Controlling for pain severity and demographics, the relationships among pain acceptance and indicators of activity, functioning, and emotional distress (i.e., anxiety and anger) were assessed in seven regression models. No significant relationships were found between self-reported physical activity or objective measurement of mean steps/day with pain acceptance. Results revealed an inverse relationship between chronic pain acceptance and pain-related functional interference (by.x = −.52, p < .01) and a positive relationship with self-reported functioning (by.x = 7.80, p < .01). A significant inverse relationship with anxiety symptoms (by.x = −1.79, p < .01) and pain acceptance was also found. Acceptance of chronic pain can facilitate decreased emotional distress, improved well-being, and better functioning and quality of life. Further investigation of chronic pain acceptance among PWH could inform the development of acceptance-based interventions.